Evaluate Toxic Effect of Bisphenol A on Kidney of Male Mice and Mitigation Its Effect by Green Tea Extract - Aamer. M. Ali (Journal of Global Pharma Technology, 2020)
Bisphenol A is a substance for the synthesis variety of plastics, primarily epoxy resins and polycarbonates. Bisphenol can have severe effects on the type and might contribute to gradual cumulative renal injury over a lifetime. This study object to estimate toxic effect of bisphenol A on type of male mice also mitigation toxic effect of bisphenol A by using extract green tea. Healthy adult male albino laboratory mice (Mus musculus) treated for two doses of bisphenol a (20 mg/kg and 40 mg/kg body weight per day) for thirty days and green tea extract was co-administration orally as antioxidant. Bio-chemical parameter of serum creatinine and blood urea was calculated as indicator of kidney function. groups treated with bisphenol A showed increased in serum creatinine and blood urea also histopathological of kidney showed significant damage in groups that treated with bisphenol A whereas groups that treated with bisphenol A and co-administration green tea extract showed mitigation toxic effect of bisphenol A due to role of green tea as anti-oxidant compound.Keywords: Evaluate, Bisphenol A, Green Tea, Antioxidant compound.